The Theory of Foreign Policy in Pericles «Funeral Oration» - Philippoussis, Yannis (Études helléniques / Hellenic Studies, 1998)
The Periclean Epitaphios has long been considered as one of the most important texts in defense of the ideal of Democracy and Freedom; it has never been considered, however, as a document in which Pericles’s theory of foreign policy is given. If Pericles had been in office for a large part of the 4th c. BC (during the Athenian hegemony and the Golden age and especially as it relates to the period of the “cold war” between the Persian and the Peloponnesian Wars), it is important to know not only his domestic and foreign policies but also the principles which guided him in his public relations and his foreign accords. It seems that the Funeral Oration gives a good account of his guiding principles. In his epigrammatic style, Pericles seems to have intended to give a clear indication of these principles and, in his cryptic way, he tries to defend their value and relevance by juxtaposing them to both the obvious Spartan principles and the not so obvious Sophistic ones which, as he had seen, would guide the Athenian domestic and foreign affairs after his death. Integral part of Thucydides’s text, and indeed an extremely significant one as it relates to the beginnings of the Peloponnesian War, Pericles’s speech becomes today as relevant as the historian’s chronicles.